2021
DOI: 10.1038/s41540-021-00206-5
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and molecular network patterns of symptom phenotypes

Abstract: Symptom phenotypes have continuously been an important clinical entity for clinical diagnosis and management. However, non-specificity of symptom phenotypes for clinical diagnosis is one of the major challenges that need be addressed to advance symptom science and precision health. Network medicine has delivered a successful approach for understanding the underlying mechanisms of complex disease phenotypes, which will also be a useful tool for symptom science. Here, we extracted symptom co-occurrences from cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 75 publications
(57 reference statements)
0
6
0
Order By: Relevance
“…We rely on a curated symptom-gene association dataset ( 28 ) (see Materials and Methods and data S1) to identify genes associated with each symptom, and then map these genes onto their corresponding proteins in the PPI (see Materials and Methods and data S2). We focus on 174 symptoms with at least 20 associated proteins.…”
Section: Resultsmentioning
confidence: 99%
“…We rely on a curated symptom-gene association dataset ( 28 ) (see Materials and Methods and data S1) to identify genes associated with each symptom, and then map these genes onto their corresponding proteins in the PPI (see Materials and Methods and data S2). We focus on 174 symptoms with at least 20 associated proteins.…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, researchers have developed a series of systems or network pharmacological strategies to detect the molecular mechanisms of TCM (Schroen, et al, 2015). A study extracted symptom co-occurrences from clinical textbooks to construct phenotype network of symptoms with clinical co-occurrence and incorporated high-quality symptom-gene associations and protein–protein interactions to explore the molecular network patterns of symptom phenotypes ( Shu, et al, 2021 ). The work of Lu et al showed that the integrated network analysis method could be used for identifying robust symptom clusters (SCs) and investigate the molecular mechanisms of these SCs, which would be valuable for symptom science and precision health ( Lu, et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Dong et al [13] constructed a mapping method for TCM prescription recommendations based on symptom term network. Shu et al [14] used network diversity to analyse protein-protein interactions in TCM symptom clusters to elucidate the potential molecular network mechanism of symptom phenotypes.…”
Section: Introductionmentioning
confidence: 99%